Camere Azzurre Costruzione di un'antologia mediterranea: da Palladio a Peter Märkli - Moschetti, Vincenzo (Premio Tesi di Dottorato, 2020)
The Mediterranean world has been seen for centuries as a 'hyperbaric chamber' in which the production of idyllic images by Grand Tour travellers has led its actual architectural evolution to the abysses, as a result of compromises in space. This has involved the construction of a (counter-)Atlas within which the architectures have acted by transfers, thus redefining the notion of geography according to space. This work investigates this 'encroaching' through the theme of the bourgeois dwelling, seeking a logical principle between the Mediterranean and the architectures by Palladio, Rossi and Märkli, united by a system of invisible distances able to demonstrate the temporariness of the 'maps'. Therefore, if it is true that the construction of space is able to change the geographical maps, it is legitimate to ask in this sense where the Mediterranean ends, a question to which this work tries to find an answer by means of the architectural project and its compositional phenomena.